Challenges in applying capacitated covering models. Issue 2 (19th January 2020) - Xu, Jing; Murray, Alan; Wang, Zifan; Church, Richard
Abstract: Service system planning has long been supported by location‐covering models designed to address access and accessibility issues. An important aspect of many systems is limits on service, often conceptualized as facility capacities. Much research can be found that proposes modeling approaches and solution techniques to account for capacitated covering problems, and commercial GIS software exists that is capable of structuring and applying facility service limits. This article reviews issues and challenges associated with the application of capacitated covering models, including critical evaluation of allocation approaches and GIS capabilities. Case studies involving service provision in two cities in California—San Jose and Santa Barbara—are provided to highlight associated issues faced in practice. While user‐friendly commercial software makes it easy to access capacitated cover models, there remain challenges for addressing underlying considerations and assumptions in practice.